STUDENTS’RESPONSES ON TASK BASED LANGUAGE TEACHING - Enny Dwi Lestariningsih; Testiana Deni Wijayatiningsih (Universitas Muhammadiyah Semarang, 2018)
When the students want to write, they need patience, grammar understanding, and reading a lot from many resources to create academic articles. These activities are still rarely done by the students from Universitas Terbuka Semarang. They tend to focus on their teaching preparation, teaching performance, lesson plan, and assessment. They think that writing research articles are difficult to do whereas their chances to gather the data are very broaden. To overcome these problems, the researchers apply Task Based Language Teaching to motivate the teachers in writing research articles and to describe their responses on Task Based Language Teaching application. The participants of this study were 28 elementary teachers who continue their study to bachelor degree at UPBJJ UT Semarang. They were in the eight semester of Pokjar Kaliwungu Kendal. They should write academic article to fulfill the tutorial task of Teknik Penulisan Karya Tulis Ilmiah subject. This research used descriptive quantitative method using students’ responses questionnaire. This research result covered that all the activities in the implementing Task Based Language Teaching were good category for the students’ responses in every phase of TBLT (pre task, main task, and post task). Moreover, the questionnaire items also got positive responses from the students’ understanding about TBLT. Keywords: Task Based Language Teaching (TBLT), students’ responses